WAVE SCATTERING WEDGE IN GAP WEDGE ANTENNAE STRUCTURES. (Sciences & Technologie. B, Sciences de l'ingénieur, 2017)
Antenna remote sensing deals with the extraction of object information from electromagnetic wave parameters. To fully exploit the potential for quantitative information acquisition, a detailed description of microwave diffusion is required. The research on this subject was mainly devoted to the far-field analysis which assumes an incident plane wave, calculates its scattered field and evaluates the radar cross section (RCS). However, under some practical conditions, far-field analysis is not valid and near-field analysis is required. In this paper, we have given a complete analysis of the near field of a corner structure due to an incident electric field from a linear source or a plane wave in the case of Gap Photonic Antennae. The far-field model, in the case of a linear source exciting the structure, is also analyzed. The interest of this study will structure the modeling process of the fields by having a clear vision of the near field which will bring a maximum of information in the process of remote sensing to help an accurate and correct decision-making.